Mechanism of methylphosphonic acid photo-degradation based on phosphate oxygen isotopes and density functional theory. Issue 54 (2nd October 2019) - Xia, Congcong; Geng, Huanhuan; Li, Xiaobao; Zhang, Yiyue; Wang, Fei; Tang, Xiaowen; Blake, R. E.; Li, Hui; Chang, Sae Jung; Yu, Chan
Abstract : Methylphosphonic acid (MPn) is an intermediate in the synthesis of the phosphorus-containing nerve agents, such as sarin and VX, and a biosynthesis product of marine microbes with ramifications to global climate change and eutrophication. Abstract : Methylphosphonic acid (MPn) is an intermediate in the synthesis of the phosphorus-containing nerve agents, such as sarin and VX, and a biosynthesis product of marine microbes with ramifications to global climate change and eutrophication. Here, we applied the multi-labeled water isotope probing (MLWIP) approach to investigate the C–P bond cleavage mechanism of MPn under UV irradiation and density functional theory (DFT) to simulate the photo-oxidation reaction process involving reactive oxygen species (ROS). The results contrasted with those of the addition of the ROS-quenching compounds, 2-propanol and NaN3 . The degradation kinetics results indicated that the extent of MPn degradation was more under alkaline conditions and that the degradation process was more rapid at the initial stage of the reaction. The phosphate oxygen isotope data confirmed that one exogenous oxygen atom was incorporated into the product orthophosphate (PO4 ) following the C–P bond cleavage, and the oxygen isotopic composition of this free PO4 was found to vary with pH. The combined results of the ROS-quenching experiments and DFT indicate that the C–P bond was cleaved by OH − /˙OH and not by other reactive oxygen species. Based on these results, we have established a mechanistic model for the photolysis of MPn, which provides new insights into the fate of MPn and other phosphonate/organophosphate compounds in the environment.